A multi-centre prospective cohort study of patients on the elective waiting list for cardiac surgery during the COVID-19 pandemic. (September 2022) - Yates, Martin T; Balmforth, Damian; Kirmani, Bilal H; Acharya, Metesh; Jeganathan, Reuben; Ngaage, Dumbor; Kanani, Mayzar; Deglurkar, Indu; Lopez-Marco, Ana; Sanders, Julie; Ye Oo, Aung
Summary: Objectives: During the worldwide COVID-19 pandemic, elective cardiac surgery was suspended to provide ICU beds for COVID-19 patients and those requiring urgent cardiac surgery. The aim of this study is to assess the effect of the pandemic on outcomes of patients awaiting elective cardiac surgery. Design: A multi-centre prospective cohort study. Setting: The elective adult cardiac surgery waiting list as of 1 March 2020 across seven UK cardiac surgical centres. Participants: Patients on the elective adult cardiac surgery waiting list as of 1 March 2020 across seven UK cardiac surgical centres. Main outcome measures: Primary outcome was surgery, percutaneous therapy or death at one year Methods: Data were collected prospectively on patients on the elective adult cardiac surgery waiting list as of 1 March 2020 across seven UK cardiac surgical centres. Primary outcome was surgery, percutaneous therapy or death at one year. Demographic data and outcomes were obtained from local electronic records, anonymised and submitted securely to the lead centre for analysis. Results: On 1 March 2020, there were 1099 patients on the elective waiting list for cardiac surgery. On 1 March 2021, 83% (n = 916) had met a primary outcome. Of these, 840 (92%) had surgery after a median of 195 (118–262) days on waiting list, 34 (3%) declined an offer of surgery, 23 (3%) had percutaneous intervention, 12 (1%) died, 7 (0.6%) were removed from the waiting list. The remainder of patients, 183 (17%) remained on the elective waiting list. Conclusions: This study has shown, for the first time, significant delays to treatment of patients awaiting elective cardiac surgery. Although there was a low risk of mortality or urgent intervention, important unmeasured adverse outcomes such as quality of life or increased perioperative risk may be associated with prolonged waiting times.